A retrospective study to analyze the pattern of referrals to the department of dermatology, venereology, and leprosy at a tertiary care center in Karnataka - Savitha Somaiah; Sneha Manjunath; T S Nagesh (Wolters Kluwer Medknow Publications, 2023)
Background: Dermatology is mainly considered as an outpatient specialty. In an institutional set up, the patients who are hospitalized in nondermatology departments may have skin diseases. The patients visiting other outpatient departments might have skin disorders. Such patients are referred to the department of dermatology and can be diagnosed and treated better in dermatology departments. Objectives: The objective was to analyze the pattern of referrals to the department of dermatology, venereology, and leprosy from other departments of the hospital. Materials and Methods: The records of the department of dermatology, venereology, and leprosy were analyzed for referrals between September 2019 and February 2020. Results: There were 214 males (46.8%) and 188 (53.2%) females in the study. The mean age of the patients in the study was 40.9 ± 20.8 years. Maximum number of referrals were received from the department of general medicine (192 cases, 47.7%), followed by general surgery (64 cases, 15.9%). Infections and infestations accounted for 183 (45.5%) cases out of the 402 referrals, and eczematous disorders were seen in 58 (14.4%) cases. The referring departments mentioned their dermatological diagnosis in 24% of the cases and were found to be correct in 18% of cases. Conclusion: The common dermatological conditions are often undiagnosed or misdiagnosed by nondermatologist, leading to incorrect treatment, and contributes to delay in treatment. By focusing on improving the training of undergraduate and postgraduate students in the conditions for which dermatology referrals are usually sought might help in improving their knowledge and later help them treat patients better.